ECTOPARASITES DISTRIBUTION OF CATFISH (Pangasius hypophthalmus) IN FISHPOND KUOK VILLAGE, BANGKINANG BARAT DISTRIC, KAMPAR REGENCY, RIAU PROVINCE - M. Yanda, M. Yanda; Syawal, Henni; Siregar, Morina Riauwaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Ectoparasites is an organism whom attach itself on the outside of host’s body. The purpose of the study was to determine distribution of ectoparasites which attack catfish in fishponds. The research was conducted in January until March 2018. Fish sample size 8-14 cm, was collected from fishponds in Kuok village, Riau Province, and identificated on Parasites and Fish Disease Laboratory of Marine and Fisheries Faculty University of Riau.The result shown that ectoparasites was found, there were; Dactylogyrus sp., Trichodina sp., Oodinium sp. The prevalence value has an average 50-60 % and intensity for each ectoparasites, there were; Dactylogyrus sp. 7-10 cell/fish, Trichodina sp. 3-5 cell/fish, and Oodinium sp. 4-5 cell/fish. Water quality in fishponds Kuok Village, Bangkinang Barat District of research shown that was normally water quality, with temperature average 27-30 0C, pH 6-7, DO 5,4-5,8 mg/L, and ammonia 0,14-0,30 mg/L. Keywrods: Catfish, Prevalence and Intensity, Ectoparasites